Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Organic ternary solar cells: A review - Ameri, Tayebeh; Khoram, Parisa; Min, Jie; Brabec, Christoph (Advanced Materials, 2013)
Recently, researchers have paid a great deal of attention to the research and development of organic solar cells, leading to a breakthrough of over 10% power conversion efficiency. Though impressive, further development is required to ensure a bright industrial future for organic photovoltaics. Relatively narrow spectral overlap of organic polymer absorption bands within the solar spectrum is one of the major limitations of organic solar cells. Among different strategies that are in progress to tackle this restriction, the novel concept of ternary organic solar cells is a promising candidate to extend the absorption spectra of large bandgap polymers to the near IR region and to enhance light harvesting in single bulk-heterojunction solar cells. In this contribution, we review the recent developments in organic ternary solar cell research based on various types of sensitizers. In addition, the aspects of miscibility, morphology complexity, charge transfer dynamics as well as carrier transport in ternary organic composites are addressed. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: dyes; IR sensitization; low bandgap polymers; organic solar cells; small molecules; ternary blends